Higher Rumination Tendency Is Associated with Reduced Positive Effects of Daily Activity Participation in People with Depressive Disorder - Lin-Jye Huang; Chinyu Wu; Hsin-Hsiu Essential Yeh; Pei-Shan Huang; Yi-Hong Yang; Yung-Chun Fang; Chien-Te Wu (Occupational Therapy International)
Objectives. Rumination, a response style characterized by self-reflection loops of negative thoughts, tends to exacerbate depressive symptoms and may impair daily functional behaviors of individuals with depression. However, the specific impacts of rumination on activity participation remain unclear. The current study was aimed at examining the differences in daily activity participation profiles between clinically depressed people with higher versus lower rumination tendencies, with the hope to provide insightful suggestions for improving the quality of life of ruminative individuals with major depression. Methods. We recruited 143 participants with a depression-related diagnosis from psychiatric daycare centers or clinics and analyzed the differences in activity participation profiles between individuals with higher versus lower rumination tendencies. Results. Although compared to those with lower rumination tendencies, participants with higher rumination tendencies spent a longer time in activity participation; they experienced lower participation quality during these activities. Furthermore, their activity participation was primarily motivated by meeting others’ expectations rather than self-interest. They also misattributed participation restriction to “lack of family support,” indicating that the unhealthy rumination pattern might be the cause of their lack of positive feelings from engaging in meaningful daily activities. Conclusions. The current results suggest that the unhealthy motivation behind activity participation seems to be an important factor that decreases the quality of participation in individuals with higher rumination tendency. Establishing a healthy motivation for activity participation is therefore critical for improving their quality of participation. As an initial step, OT interventions could put a focus on helping them clarify and escape from the source of negative rumination cycles that impede their positive feeling of activity participation.